Concept for evaluating the safety of a dynamically loaded gearbox reducer - Elizabeta Hristovska (Acta Polytechnica)
The safety of dynamically loaded gearbox reducers is of interest to companies and the scientific community, and any research and conclusion in this direction is a significant contribution, as this problem has not been widely discussed in scientific articles. This article presents a concept for evaluating the safety of a dynamically loaded reducer, specifically built into a rotating excavator used in surface coal mines for its working wheel. The presented concept offers three ways to evaluate safety: according to factors of safety, according to operating parameters, and according to load capacity and loads. A methodology was presented for all three ways, which was applied to a specific reducer under specific working conditions, and output results were obtained. The output results were analysed and conclusions were drawn using the specific reducer. However, it was established, based on the author’s experience, that these results can be generalised for similar reducers operating under the same or similar working conditions. The set concept can be applied to the safety assessment of other dynamically loaded gear reducers.